Pengembangan Aplikasi Mobile (E-Tani) Pencari Tenaga Tani Pangan Menggunakan Metode Location Based Service Berbasis People Nearby (Studi Kasus Desa Kenduruan Kabupaten Tuban Provinsi Jawa Timur) - Pramudya Vizkal Arfianto; Herman Tolle; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Agriculture in Indonesia is an important pillar in the economic sector which contributes a lot in the field of food. Kenduruan Subdistrict in Tuban Regency, East Java is a rural area with the majority of the population being farmers, where most farmers manage privately owned rice fields so that people who own rice fields rather than their background as farmers will find it difficult to manage their fields, thus requiring farmers who are not currently managing rice fields. anyone and has become a common problem of the difficulties faced by the rice field owners in Kenduruan Village. So we need an Android-based cellular application that can help rice owners find farmers by recommending farmers who are closest to their access location. This application called e-Tani was built by applying the Location Based Service method and the Haversine Formula so that it will be optimal when used. The results of testing the application Blackbox are worth 100% and have a functional otherwise valid. The next test result is usability testing, where the test is carried out to find out the ease when using the application, and from the usability test, the results are as much as 100% from both categories of users, namely rice field owners and farmers. Then 0.135 goals/sec in the rice field owner, and 0.017 goals/sec for the farmer in the aspect of efficiency, then 4.28 in the rice field owner, and 4.4 for the farmer in the satisfaction aspect, so it can be stated that the e-Tani application is acceptable in the community.